Refugee Welfare Dependancy Rates in the U.S. - A., H. (Refuge: Canada's Journal on Refugees, 1983)
In the December 1982 issue of Refuge (Vol. 2, No. 2), we published an article criticizing the distorted use of refugee dependency rates in the U.S. Congress. The Refugee Policy Group published an analysis of the meaning of Welfare Dependency Rates as an Indication of the Adaptation of Indochinese Refugees in the U.S.